Entrepreneurial culture, personal character, emotional intelligence toward improves entrepreneurs’ independence - Qurnain, Nuzulul; Risal, Zef; Maulana, Wahyu (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This research aims to test and analyze whether personal character and emotional intelligence mediate entrepreneurial culture on the independence of cigarette entrepreneurs in Pamekasan, Madura. Method – This type of research is quantitative research with an associative approach. Data was collected using a questionnaire, and the research objectives were cigarette entrepreneurs in all sub-districts in Pamekasan Madura Regency. The population in this study was 1262 people, and the sample was 126 entrepreneurs. Purposive sampling techniques were used with predetermined criteria. Testing research hypotheses using AMOS SEM. Findings – The research results show that entrepreneurial culture positively affects entrepreneurial independence. Entrepreneurial culture positively affects personal character. Entrepreneurial culture positively affects emotional intelligence. Personal characters cannot mediate the influence of entrepreneurial culture on entrepreneurial independence. Emotional intelligence cannot mediate the influence of entrepreneurial culture on entrepreneurial independence. Implications – Theoretical implications have contributed to expanding scientific knowledge regarding the theory of entrepreneurial culture to increase business independence. Practical implications of the culture of the surrounding community need to be preserved because it influences increasing independence through personal character, namely thinking before acting, daring to take risks for future life and emotional intelligence, and the ability to recognize one's own emotions and the emotions of others.